Minimising carbon and financial costs of steam sterilisation and packaging of reusable surgical instruments. Issue 2 (28th November 2021) - Rizan, Chantelle; Lillywhite, Rob; Reed, Malcolm; Bhutta, Mahmood F
Abstract: Background: The aim of this study was to estimate the carbon footprint and financial cost of decontaminating (steam sterilization) and packaging reusable surgical instruments, indicating how that burden might be reduced, enabling surgeons to drive action towards net-zero-carbon surgery. Methods: Carbon footprints were estimated using activity data and prospective machine-loading audit data at a typical UK in-hospital sterilization unit, with instruments wrapped individually in flexible pouches, or prepared as sets housed in single-use tray wraps or reusable rigid containers. Modelling was used to determine the impact of alternative machine loading, opening instruments during the operation, streamlining sets, use of alternative energy sources for decontamination, and alternative waste streams. Results: The carbon footprint of decontaminating and packaging instruments was lowest when instruments were part of sets (66–77 g CO2 e per instrument), with a two- to three-fold increase when instruments were wrapped individually (189 g CO2 e per instrument). Where 10 or fewer instruments were required for the operation, obtaining individually wrapped items was preferable to opening another set. The carbon footprint was determined significantly by machine loading and the number of instruments per machine slot. Carbon and financial costs increased with streamlining sets. High-temperature incineration of waste increased the carbon footprint of single-use packaging by 33–55 per cent, whereas recycling reduced this by 6–10 per cent. The absolute carbon footprint was dependent on the energy source used, but this did not alter the optimal processes to minimize that footprint. Conclusion: Carbon and financial savings can be made by preparing instruments as part of sets, integrating individually wrapped instruments into sets rather than streamlining them, efficient machine loading, and using low-carbon energy sources alongside recycling. Abstract : Carbon and financial savings can be made by opting to prepare instruments as part of sets rather than individually wrapped items in single-use polypropylene pouches, efficient loading of decontamination machines, and recycling. Streamlining instrument sets (by removing infrequently used instruments) counterintuitively increased the carbon footprint and financial cost. The absolute carbon footprint was dependent on the energy source used for decontamination, but this did not alter the optimal processes to minimize that footprint.